Location-level processes drive the establishment of alien bird populations worldwide - Redding, David W.; Pigot, Alex L.; Dyer, Ellie E.; Şekercioğlu, Çağan H.; Kark, Salit; Blackburn, Tim M. (Nature (London), 2019)
Human-mediated translocation of species to areas beyond their natural distribution (which results in ‘alien’ populations 1 ) is a key signature of the Anthropocene 2 , and is a primary global driver of biodiversity loss and environmental change 3 . Stemming the tide of invasions requires understanding why some species fail to establish alien populations, and others succeed. To achieve this, we need to integrate the effects of features of the introduction site, the species introduced and the specific introduction event. Determining which, if any, location-level factors affect the success of establishment has proven difficult, owing to the multiple spatial, temporal and phylogenetic axes along which environmental variation may influence population survival. Here we apply Bayesian hierarchical regression analysis to a global spatially and temporally explicit database of introduction events of alien birds 4 to show that environmental conditions at the introduction location, notably climatic suitability and the presence of other groups of alien species, are the primary determinants of successful establishment. Species-level traits and the size of the founding population (propagule pressure) exert secondary, but important, effects on success. Thus, current trajectories of anthropogenic environmental change will most probably facilitate future incursions by alien species, but predicting future invasions will require the integration of multiple location-, species- and event-level characteristics. Bayesian hierarchical regression analysis of a global database of bird introduction events reveals the environmental, climatic and biotic factors that are the primary determinants of the successful establishment of populations of alien species.